Effectiveness of Project-Based Learning Combined With Outdoor Study on Students' Mental Map - Rosyida, Fatiya; Wirahayu, Yuswanti Ariani; Insani, Nailul (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
Mental maps can be used as an effort to determine the understanding of students' spatial patterns. Mental maps can also be used to measure students' perceptions of environmental characteristics. A good mental map ability can also help students understand spatial information. Geography learning provides various kinds of spatial information so that a mental map is needed to assist in completing the learning. Besides, geography learning must also be able to improve students' understanding of spatial information. Therefore, improving the ability of the student mental map is important. This study aims to improve the mental map of high school students through project-based learning combined with outdoor study. Research is a quasy experiment using post-test only control design. The research hypothesis test uses an Independent sample T-Test. The results showed that the experimental class had a higher average value compared to the control class.